2021
DOI: 10.1155/2021/5533086
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Properties of Argillaceous Intercalation under the Combination of Static and Intermittent Dynamic Shear Loads

Abstract: The construction and long-term operation stage of the rock slope with argillaceous interlayer will be subjected to intermittent dynamic loads, such as blasting and earthquake. For the argillaceous interlayer in the rock slope, its rheological properties are not only related to the initial stress state caused by the gravity of the overlying rock mass but also affected by intermittent dynamic loads. In order to investigate the rheological properties of argillaceous intercalation under the combination of static a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Ma et al explored the effect of water content and normal stress in remodeling samples on the shear strength of weak interlayers 6 ; Zhang et al carried out the rheological test of muddy interlayers under the combined action of static shear and discontinuous dynamic shear. It was found that when the static shear stress was close to the shear strength, the intermittent dynamic disturbance would significantly affect the deformation of muddy interlayers 7 ; Qin et al explored the decay behaviour of the dynamic damping ratio of the muddy interlayer under small to medium strains and used a modified model to describe its relationship with dynamic strain, confining pressure, water content and clay content, revealing the influence of different factors on the dynamic damping ratio 8 ; Guo et al investigated the creep property and long-term strength of clay-type muddy interlayers under different normal stresses 9 ; Liu et al found that the shear stress-shear displacement curve was slip type, the shear strength decreased with the increase of water content, the internal friction angle decreased gradually, and the cohesive force showed a non-monotonic change through the direct shear test of red sandstone muddy interlayer with different water content and normal stress, indicating that there was a critical water content, and the cohesive force showed different trends before and after this value 10 ; Xu et al measured the real strength parameters of the weak interlayer on the sliding surface of Jiuding Mountain, and found that the failure of the weak interlayer began at the contact between the clay filler and the limestone boundary, rather than the clay material itself 11 ; Xue et al carried out indoor dynamic triaxial tests on the muddy interlayer of the left bank of the Xiaolangdi project. It was found that under the lower total shear stress, the deformation of the sample gradually stabilized with the increase of the number of vibrations, and the dynamic strength decreased with the increase of the number of vibrations, and finally stabilized after thousands of vibrations 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Ma et al explored the effect of water content and normal stress in remodeling samples on the shear strength of weak interlayers 6 ; Zhang et al carried out the rheological test of muddy interlayers under the combined action of static shear and discontinuous dynamic shear. It was found that when the static shear stress was close to the shear strength, the intermittent dynamic disturbance would significantly affect the deformation of muddy interlayers 7 ; Qin et al explored the decay behaviour of the dynamic damping ratio of the muddy interlayer under small to medium strains and used a modified model to describe its relationship with dynamic strain, confining pressure, water content and clay content, revealing the influence of different factors on the dynamic damping ratio 8 ; Guo et al investigated the creep property and long-term strength of clay-type muddy interlayers under different normal stresses 9 ; Liu et al found that the shear stress-shear displacement curve was slip type, the shear strength decreased with the increase of water content, the internal friction angle decreased gradually, and the cohesive force showed a non-monotonic change through the direct shear test of red sandstone muddy interlayer with different water content and normal stress, indicating that there was a critical water content, and the cohesive force showed different trends before and after this value 10 ; Xu et al measured the real strength parameters of the weak interlayer on the sliding surface of Jiuding Mountain, and found that the failure of the weak interlayer began at the contact between the clay filler and the limestone boundary, rather than the clay material itself 11 ; Xue et al carried out indoor dynamic triaxial tests on the muddy interlayer of the left bank of the Xiaolangdi project. It was found that under the lower total shear stress, the deformation of the sample gradually stabilized with the increase of the number of vibrations, and the dynamic strength decreased with the increase of the number of vibrations, and finally stabilized after thousands of vibrations 12 .…”
Section: Introductionmentioning
confidence: 99%